Sodium‐glucose co‐transporter protein 2 inhibitors for long-term kidney function preservation in type 2 diabetes with chronic kidney disease: a meta-analysis of rates of progression to end-stage renal disease - Algethami, Mohammed D.; Alzahrani, Sami A.; Alessa, Bander H.; Madhi, Asayil N. Bin; Alzahrani, Hamzah M.; Altwairqi, Rami S. (International Journal Of Community Medicine And Public Health, 2024)
Chronic kidney disease (CKD) is a major complication of type 2 diabetes mellitus (T2DM) and a leading cause of end-stage renal disease (ESRD). Sodium-glucose co-transporter 2 (SGLT2) inhibitors have demonstrated renoprotective effects in clinical trials, but their precise impact on ESRD risk remains to be comprehensively quantified. This study aimed to evaluate the effectiveness of SGLT2 inhibitors in reducing ESRD risk in T2DM patients with CKD by synthesizing evidence from randomized controlled trials. A meta-analysis was conducted using data from eight randomized controlled trials involving 28,253 participants. Studies comparing SGLT2 inhibitors with placebo in T2DM patients with CKD were included. The primary outcome was the risk of ESRD, reported as a pooled risk ratio (RR) with 95% confidence intervals (CIs). Heterogeneity was assessed using the I² statistic. The pooled analysis demonstrated a significant reduction in ESRD risk with SGLT2 inhibitors compared to placebo (RR, 0.73; 95% CI, 0.66–0.82), indicating a 27% risk reduction. Heterogeneity was low (I²=0%; p=0.50), confirming consistency across trials. Subgroup analyses showed similar reductions across different CKD stages and follow-up durations. In conclusion, SGLT2 inhibitors significantly reduce the risk of ESRD in T2DM patients with CKD, highlighting their renoprotective potential. These findings support the integration of SGLT2 inhibitors into standard care for high-risk populations to delay CKD progression and prevent ESRD.